Multimorbidity in cardiovascular disease and association with life satisfaction: a Chinese national cross-sectional study. Issue 12 (24th December 2020) - Liu, Guihao; Xue, Yunlian; Liu, Yuanhui; Wang, Sheng; Geng, Qingshan
Abstract : Background: The coexistence of multiple chronic conditions is very common in cardiovascular disease (CVD). However, the prevalence of CVD multimorbidity in China and its influence on life satisfaction have not been reported. This study aimed to investigate the proportions of 12 chronic comorbid diseases in CVD and the associations of multimorbidity with life satisfaction in patients with CVD. Methods: We conducted a cross-sectional study in a nationally representative sample of 3478 participants with CVD aged 45 years or more who participated in the China Health and Retirement Longitudinal Study 2015. Correlations of multimorbidity with 12 chronic diseases in CVD and life satisfaction were investigated using logistic regression models, after adjusting for 12 covariates. Results: The proportion of multimorbidity among participants with CVD was 93.3% (89.4% for middle-aged adults and 95.4% for older adults; 92.9% for men and 93.5% for women). The proportion of participants with CVD multimorbidity who were dissatisfied with life was 11.2%, significantly higher than those without any chronic diseases (χ 2 =5.147, p=0.023). Life satisfaction in patients with CVD decreased with increased number of comorbidities (χ 2 =45.735, p<0.001). Kidney disease (OR=1.933, 95% CI: 1.483 to 2.521), memory-related diseases (MRDs) (OR=1.695, 95% CI: 1.149 to 2.501) and dyslipidaemia (OR=1.346, 95% CI: 1.048 to 1.729) were significantly associated with reduced life satisfaction when adjusting for 12 covariates. Conclusions: In this nationally representative cross-sectional study, life satisfaction was reduced by multimorbidity of CVD. Kidney disease had the greatest influence on life satisfaction in patients with CVD, followed by dyslipidaemia and MRDs. Our study emphasises the importance of preventing of chronic diseases in adults with CVD.